THE TEACHER AS A SUBJECT OF THE PEDAGOGICAL PROCESS - Axmadjonova Oydinoy; No'monjonova Gulnoza (Ta’lim innovatsiyasi va integratsiyasi, 2025)
Abstract This article explores the essential role of the teacher as a subject of the pedagogical process. It examines the teacher’s influence not only as a source of knowledge but also as a guide, motivator, and moral model for students. The article highlights the key responsibilities, professional competencies, and human qualities required for effective teaching. It also underlines the importance of teacher-student interaction, self-reflection, and continuous professional development in shaping an effective educational environment.